Analisis Kinerja Keuangan Melalui Rasio Non Performing Loan pada PT BPR Mitra Daya Mandiri - Fatin, Ragil Latifah; Andrianto, Toni; Munawar, Aang (Jurnal Aplikasi Bisnis Kesatuan, 2024)
Financial report analysis is very necessary for companies so that financial reports are easier to understand and comprehend by various users of financial reports in making decisions. In the analysis of financial reports will produce a measurement of financial performance in the company in a certain period, to measure financial performance can use financial ratios.To measure financial performance against non-performing loans (doubtful, substandard, bad) can use the Non Performing Loan (NPL) ratio. The Non Performing Loan (NPL) ratio contains the amount of non-performing loans (doubtful, substandard, bad) compared to the total credit provided by the bank. So that this ratio can help companies in knowing credit risk. In this final assignment, the analysis of financial performance at PT BPR Mitra Daya Mandiri uses financial reports in 2020 - 2022. Financial performance through the Non Performing Loan (NPL) ratio is still in a healthy condition based on Bank Regulation No. 13/1/PBI/2011. Although the Non Performing Loan (NPL) ratio has increased in problematic loans (doubtful, non-performing and bad) that occurred in 2020 - 2022. Keywords: financial report analysis, financial ratio, Non Performing Loan (NPL) ratio